Respuesta :

Answers: (a→b), (b→a), (c→c)

Explanation:

Column A:

a) [tex]y = -3x + \dfrac{1}{3}[/tex]

  m = -3  ⇒  m⊥ = [tex]\dfrac{1}{3}[/tex]


b) 6x - 2y = 4

         -2y = -6x + 4

            y =  3x - 2

  m = 3  ⇒  m⊥ = [tex]-\dfrac{1}{3}[/tex]


c) y - 3 = [tex]\dfrac{1}{3}[/tex](x - 3)

  m = [tex]\dfrac{1}{3}[/tex] ⇒  m⊥ = -3


Column B

a) y - 3 = [tex]-\dfrac{1}{3}[/tex](x - 3)

  m = [tex]-\dfrac{1}{3}[/tex]


b) y = [tex]\dfrac{1}{3}x + 6[/tex]

   m = [tex]\dfrac{1}{3}[/tex]


c) 3x + y = 3

           y  = -3x + 3

  m = -3

******************************************************************************

Column A letter a matches to Column B letter b

Column A letter b matches to Column B letter a

Column A letter c matches to Column B letter c